2007
DOI: 10.1002/adv.20090
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic silicone elastomer lubricant in extrusion of polypropylene wood flour composites

Abstract: ABSTRACT:A possibility of using a thermoplastic silicone elastomer (TPSE) for reduction of surface defects in the extrusion of wood-filled metallocene polypropylene (mPP) has been investigated in this work. A capillary rheometer and a single-screw extruder have been utilized to study the effect of the additive on the extrudate distortions. Maleated syndiotactic metallocene polypropylene was also used as an adhesion promoter in mPP/wood flour composites. At loadings of 50 wt% wood flour in the mPP, the extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Viscosity can be as high as 1–10 kPa s in the case of 50 wt.% wood loading at low shear rates (100 s −1 ). The wood content has also a great influence on the wall slip behavior, with slip velocity increasing with the amount of natural filler [ 33 , 43 , 52 , 54 , 58 , 59 , 60 , 61 , 67 ]. Slip velocity is of the order of 1–10 mm/s at a 200 kPa applied shear stress.…”
Section: Wood Polymer Composites Characterization With Pressure-drmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosity can be as high as 1–10 kPa s in the case of 50 wt.% wood loading at low shear rates (100 s −1 ). The wood content has also a great influence on the wall slip behavior, with slip velocity increasing with the amount of natural filler [ 33 , 43 , 52 , 54 , 58 , 59 , 60 , 61 , 67 ]. Slip velocity is of the order of 1–10 mm/s at a 200 kPa applied shear stress.…”
Section: Wood Polymer Composites Characterization With Pressure-drmentioning
confidence: 99%
“…Several studies focused on the choice of the most suitable additives to obtain a product with optimal physical and mechanical performance. The most important additives of WPCs are coupling agents and lubricants [ 48 , 53 , 58 , 61 , 63 , 64 , 67 , 68 , 73 ].…”
Section: Wood Polymer Composites Characterization With Pressure-drmentioning
confidence: 99%
“…showed that the torque and melt pressure during extrusion and the apparent shear viscosity measured by capillary rheometer gradually decreased with the increase of lubricant content in the WPC formulation. Hristov and Vlachopoulos used a low concentration of 1 wt % thermoplastic silicone elastomer in the extrusion of WPC to reduce or even completely eliminate the surface tearing and increase the extrusion speed. Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Adhikary et al 23 showed that the torque and melt pressure during extrusion and the apparent shear viscosity measured by capillary rheometer gradually decreased with the increase of lubricant content in the WPC formulation. Hristov and Vlachopoulos 24 used a low concentration of 1 wt % thermoplastic silicone elastomer in the extrusion of WPC to reduce or even completely eliminate the surface tearing and increase the extrusion speed. Chen et al 25 found that the torque of the Pithecellobium Clypearia Benth Fiber (PCBF)/recycled Acrylonitrile-Butadiene-Styrene (ABS) composite decreased with an increase of the TPW604 lubricant content.…”
Section: Introductionmentioning
confidence: 99%
“…The design of a new product and corresponding extrusion die, must take into account several issues namely, achievement of balanced flow [2][3][4], avoidance of rheological defects, maximization of the production rate [5][6][7] and maintenance, or increase, of the product quality [1]. Profiles like window frames and catheters, are some of the applications that involve the most complex cross-section geometries produced by extrusion.…”
Section: Introductionmentioning
confidence: 99%